Nonfrequent but well‐documented, rare and very rare HLA alleles observed in the Croatian population. Issue 6 (December 2014) - Grubic, Z.; Burek Kamenaric, M.; Maskalan, M.; Stingl Jankovic, K.; Zunec, R.
Abstract The aim of the study was to evaluate the presence of nonfrequent, rare and very rare alleles among Croats and to estimate whether they are associated with specific alleles at other human leukocyte antigen (HLA) loci. This retrospective study included the typing results from the last 10 years; total number of individuals included was approximately 45, 000. Among 17 alleles so far observed only once in our population, 6 (A*24:41, B*07:02:28, B*35:03:03, B*39:40N, DRB1*13:23 and DRB1*14:111) belong to very rare alleles, 2 (B*44:16 and DRB1*01:31) belong to rare alleles according to the 'Rare Alleles Detector' tool ( www.allelefrequencies.net), while for the B*35:101:01 allele published data exist only in the IMGT/HLA database. The remaining eight HLA alleles observed only once among Croats are considered as frequent according to the 'Rare Alleles Detector'. Those 17 HLA alleles are not declared as common well defined (CWD) alleles in the CWD allele catalogue 2.0.0. Haplotype analysis of nonfrequent alleles detected in our sample supports the idea that different populations, although similar in some aspects regarding HLA allele and haplotype distribution, still have some unique characteristics. This is the case for A*01:02, B*39:10 and DRB1*13:32 which form haplotypes unreported to date among our subjects.